2018
DOI: 10.3390/nano8070539
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Cytotoxicity and Morphological Assessments of GO-ZnO against the MCF-7 Cells: Determination of Singlet Oxygen by Chemical Trapping

Abstract: Graphene-based materials have attracted considerable interest owing to their distinctive characteristics, such as their biocompatibility in terms of both their physical and intrinsic chemical properties. The use of nanomaterials with graphene as a biocompatible agent has increased due to an uptick in dedication from biomedical investigators. Here, GO-ZnO was characterized by X-ray diffraction (XRD), field emission scanning electron microscopy (FESEM), ultraviolet-visible (UV-Vis) spectroscopy, energy dispersiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(14 citation statements)
references
References 64 publications
2
12
0
Order By: Relevance
“…Moreover, the highest LDH release was in CuO NPs (100 mg/ml) with R þ H groups as compared to control. Shaheen et al revealed that assessments of the GO-ZnO against the MCF-7 Cells, a significant increased the LDH release in a dose-dependent manner [40].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the highest LDH release was in CuO NPs (100 mg/ml) with R þ H groups as compared to control. Shaheen et al revealed that assessments of the GO-ZnO against the MCF-7 Cells, a significant increased the LDH release in a dose-dependent manner [40].…”
Section: Discussionmentioning
confidence: 99%
“…•− ), hydroxyl radical (HO•), and hydrogen peroxide (H 2 O 2 ) serve as signaling molecules in the process of apoptosis [46]. The GO-ZnO nanocomposite was found to induce oxidative stress mediated toxicity in MCF-7 cells [47]. In this study, we examined several parameters of oxidative stress in A549 cells against CeO 2 NPs, RGO, and CeO 2 -RGO nanocomposite when exposed to said particles for 24 h. The quantitative data demonstrated that the intracellular level of ROS in the CeO 2 NP group was almost similar to that of the control group, but significantly higher than the RGO group ( Figure 8A).…”
Section: Oxidative Stressmentioning
confidence: 99%
“…The cellular morphology of HUH-7 and WRL-68 cells were thoroughly studied, after treatment, under the phase-contrast microscope, and images were taken by Olympus camera for further comparison. In published studies, distortion of cellular morphology along with membrane disintegration, changed in shape and size is an indication of molecular responses because of nanoparticles [91]. Hence, we verified and compared the prominent effect of IONP with 5FU and hygromycin B on the cellular morphology.…”
Section: Mechanism Of Photocatalytic Degradationmentioning
confidence: 57%